Seminal attributes of Vechur bulls (Bos indicus), the smallest humped dairy cattle - S, SUDHEER; ROSE, DEEPTHI S S; J, ANOOP (The Indian Journal of Animal Sciences, 2021)
The study was undertaken at Mattupatti semen station to objectively evaluate the seminal attributes of frozenthawed semen of Vechur bulls, the smallest humped dairy cattle in the world, using the computer assisted semen analyzer (CASA) and Flow cytometer. The mean motility and progressive motility of the frozen-thawed semenestimated via CASA was 77.25±9.56 and 64.0±4.21% respectively. Mean values obtained for the sperm kinetic parameters like path velocity (VAP), progressive velocity (VSL), track speed (VCL), lateral head amplitude (ALH),beat cross frequency (BCF), straightness (STR) and linearity (LIN) were 82.56±12.12, 76.22±10.38, 107.77±21.42, 4.39±0.91, 20.87±3.81, 92.37±3.25 and 72.87±6.64% respectively. Flow cytometry analysis of the functional sperm parameters like sperm viability, live sperms with intact acrosome, sperms with normal mitochondrial membranepotential (MMP) and sperms with altered DNA were 81.67±4.55, 76.16±9.76, 82.40±5.61 and 11.75±0.3% respectively. The mean value of the HOS reactive sperms was 71.81±5.71%. Mean values for the length and width of the sperm head, length of mid-piece, tail and overall sperm length measured by computer image analysis was 8.99±0.36, 5.07±0.23, 14.21±0.35, 45.12±1.53 and 68.32±1.41 μm respectively. Study concluded that seminal attributes of Vechur bulls could be estimated with CASA and Flow cytometer and the parameters were comparable to other indigenous, crossbreds and exotic dairy cattle.